The Aron Museum at Temple Emanu-El-Beth Sholom in Montreal - Lerner, Loren (Material Culture Review, 2006)
In 1953, when the Aron Museum at the Temple Emanu-El-Beth Sholom in Montreal opened it was the first museum of Jewish ceremonial objects in Canada. In its early years, Rabbi Stern—in his vision of the collection, the Aron family as benefactors and the artist Sam Borenstein who helped to select the pieces, played significant roles in the development of the museum. This article explores the original description of the Aron Museum to show how the humanistic and aesthetic values attributed to the items followed the pattern of pre-Holocaust Jewish museums and exhibitions. For a variety of reasons the religious, ethnographic and historical interpretations of the ceremonial objects of the Aron Museum were initially minimized in its public display. Today, the provenance and memory associations of these objects as well as an explanation of Jewish rituals more fully express the multi-layered meaning of Jewish ceremonial art. Résumé Lorsque le musée Aron ouvrit ses portes en 1953, au temple Emanu-El-Beth Sholom à Montréal, il était le premier musée d’objets cérémoniels juifs au Canada. Durant ses premières années d’existence, le rabbin Stern, avec sa conception de la collection, les membres de la famille Aron en tant que bienfaiteurs et l’artiste Sam Borenstein, qui contribua à sélectionner les objets, jouèrent des rôles significatifs dans son développement. Cet article explore la description originelle du musée Aron afin de montrer la manière dont les valeurs humanistes et esthétiques attribuées aux pièces exposées suivaient le schéma des musées et expositions juives d’avant l’Holocauste. Pour des raisons variées, les interprétations religieuses, ethnographiques et historiques des objets cérémoniels du musée Aron était initialement minimisées dans l’exposition publique. Aujourd’hui, la provenance et les associations mémorielles de ces objets, aussi bien que l’explication des rituels juifs, expriment plus pleinement la signification multi-niveaux de l’art cérémoniel juif.